A versatile approach to the synthesis of mannosamine glycosides. Issue 34 (19th August 2020) - Alex, Catherine; Visansirikul, Satsawat; Demchenko, Alexei V.
Abstract : The 3- O -picoloyl protected glycosyl donor provides high β-manno stereoselectivity, whereas 3- O -benzoylated donor leads to complete α-manno stereoselectivity. Abstract : O -Picoloyl protecting groups at remote positions can affect the stereoselectivity of glycosylation by means of the H-bond-mediated aglycone delivery (HAD) pathway. A new practical method for the stereoselective synthesis of β-glycosides of mannosamine is reported. The presence of the O -picoloyl group at the C-3 position of a mannosamine donor can provide high or complete stereocontrol. The method was also utilized for the synthesis of a biologically relevant trisaccharide related to the capsular polysaccharide of Streptococcus pneumoniae serotype 4. Also reported herein is a method to achieve complete α-manno stereoselectivity with mannosamine donors equipped with 3- O -benzoyl group.